THE HADITH SCHOLARSHIP OF IMAM AL-TIRMIDHI AND ITS INFLUENCE ("XXI ASRDA INNOVATSION TEXNOLOGIYALAR, FAN VA TAʼLIM TARAQQIYOTIDAGI DOLZARB MUAMMOLAR" nomli respublika ilmiy-amaliy konferensiyasi, 2026)
Imam al-Tirmidhi is one of the most distinguished scholars in the history of Islamic hadith studies. His full name was Abu Isa Muhammad ibn Isa ibn Sawrah al-Tirmidhi, and he was born in Tirmidh, a historic city in present-day Uzbekistan. He became famous for his deep knowledge of hadith, his careful method of narration, and his unique contribution to the classification and evaluation of hadith reports. His most famous work, Jami‘ al-Tirmidhi, also known as Sunan al-Tirmidhi, is one of the six major canonical hadith collections in Sunni Islam. Unlike many earlier compilations, Imam al-Tirmidhi’s work is especially valuable because he not only collected hadiths but also explained their legal relevance, assessed their authenticity, mentioned the opinions of Islamic jurists, and introduced technical hadith terms such as hasan in a systematic way. His scholarship had a lasting influence on hadith methodology, Islamic jurisprudence, and the intellectual heritage of the Muslim world